2015
DOI: 10.1108/josm-01-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Domestic versus offshore service providers

Abstract: Purpose -Prior research has determined that consumers are opposed to services offshoring. The purpose of this paper is to determine the likelihood that consumers would choose a domestic vs an offshore service provider if asked to pay more, wait longer, or sacrifice service quality. Design/methodology/approach -The cost, time to wait, and quality of services provided (for two different services: taxes and customer service) were varied to determine respondent likelihood to choose a domestic as opposed to an offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…After the research was carried out, the authors found that macro factors in terms of information, cleanliness and services have the highest positive effect on the overall quality of service. Domestic, in relation to foreign service providers, with an emphasis on the impact of the cost, time and quality of the victim on the choice of consumers, is the research which was done by Andrej M. Forman et al (2015). The results support the idea that while consumers significantly prefer domestic, rather than foreign service providers, providers are not willing to accept a monetary or time-sacrifice to allow them access.…”
Section: Overview Of the Research In The Field Of The Service Systemsmentioning
confidence: 89%
“…After the research was carried out, the authors found that macro factors in terms of information, cleanliness and services have the highest positive effect on the overall quality of service. Domestic, in relation to foreign service providers, with an emphasis on the impact of the cost, time and quality of the victim on the choice of consumers, is the research which was done by Andrej M. Forman et al (2015). The results support the idea that while consumers significantly prefer domestic, rather than foreign service providers, providers are not willing to accept a monetary or time-sacrifice to allow them access.…”
Section: Overview Of the Research In The Field Of The Service Systemsmentioning
confidence: 89%
“…In the study of McGuire, Kimes, Lynn, Pullman, and Lloyd (2010), it was claimed that providing entertainment to customers during the period of waiting can reduce their boredom and produce a positive evaluation on their WTS. In another study, Forman, Thelen, and Shapiro (2015) investigated the customers' assessment of the off-shoring of services and established that there will be a decrease in the customers' loyalty towards the domestic service provider if the WT is longer and if their international counterpart provides the same service better and quicker.…”
mentioning
confidence: 99%